THE URGENCY OF AN INCLUSIVE SOCIETY BASED ON ISLAMIC VALUES FOR PERSONS WITH DISABILITIES - Mirza Dwi Permana; Khalif Oktifan Yani (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This research explores the urgency of developing an inclusive society based on Islamic values for persons with disabilities in Indonesia through a qualitative literature review approach. Comprehensive analysis of academic literature from 2020-2025 reveals that integrating Islamic principles with the concept of inclusive society requires paradigmatic transformation in understanding disability as diversity of Allah's creation. Research findings indicate that Islamic values such as rahma, ta'awun, and musawah provide strong theological foundations for inclusive society development, yet implementation faces complex structural and cultural challenges. Investigation of inclusive education in Islamic institutions indicates significant potential for transformation, while analysis of stigmatization and accessibility reveals the need for comprehensive strategies integrating education, advocacy, and community empowerment dimensions. Effective inclusive society development strategies must accommodate intersections between Islamic values and universal human rights principles, while considering Indonesia's unique socio-cultural context.